Development of Learning Media Using Smart Apps Creator Based on Problem Based Learning for Social Science Learning in Grade IV of Elementary School - Raidha Elsa Aprilianti; Yeni Erita (JURNAL PENDIDIKAN IPS, 2025)
This study aims to develop a learning media using Smart Apps Creator with a PBL approach that is valid, practical, and effective. The method employed is Research and Development (R&D) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The designed media was validated by subject matter experts, language experts, and media experts, and was also tested for its practicality and effectiveness through questionnaires and learning outcome tests. The findings indicate that the learning media is valid, practical, and effective for use in the teaching and learning process. The validation score from the three validators reached 91%, categorized as "Highly Valid." Based on the questionnaire responses from teachers and students at the pilot school, SDN 21 Bandar Buat, the media was considered highly practical with practicality percentages of 94.28% and 96.58%, respectively. At SDN 01 Bandar Buat, the practicality scores were 97.14% and 91.21%, while at SDN 11 Indarung, the scores were 94.28% and 94%. The product's effectiveness was reflected in the improvement of student learning outcomes, with N-gain scores of 86.96% at SDN 21 Bandar Buat, 90.51% at SDN 01 Bandar Buat, and 88.72% at SDN 11 Indarung, all of which fall into the "Effective" category.